Entre potências e resistências: o Centro de Atenção Psicossocial Infantojuvenil e a construção da lógica da atenção psicossocial - Zaniani, Ednéia José Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper aims to reflect on the care effectiveness initiatives in mental health Psychosocial Care Children and Youth Centre (CAPSi) and its intersection with the logic of Psychosocial Care. Constructed within the Movement of the Brazilian Psychiatric Reform, the psychosocial care has been defined as a set of actions capable of constituting a new paradigm for the practices in mental health that outweighs the asylum model. Among the suggested actions in this process, CAPSi, part of the substitute service network, has been considered the most concrete initiative of the State to move into the public sphere care for the mental health of children and adolescents in serious and persistent psychological distress, unable or affected in some way in their capacity to maintain or establish social ties and life projects. The Psychosocial Care pleads that the CAPSi isn't only a mere service, unlike the doctor-centered work, specialized and individualized, mediates the (re)social and community inclusion, giving the organization an extended care network. Guided by socio-historical perspective we seek the conceptions that mark the current practices, so we access documentary sources CAPSi in order to identify the profile of children and adolescents referred, which institutions they wew sent to, what reasons lead configure the demand for care and the outcomes of their cases. In addition to that, we conducted focus groups (GD) with professional CAPSi and monitor, through participant observation, teamwork routine and their integration in multidisciplinary meetings in Psychosocial Care Network (RAPS). The insertion in the field presented in childhood conceptions, adolescence and mental health naturalized outline their own way the content of the aspirated practices for intra and inter-sectoral network and measures imposed by CAPSi professionals. Boys are more directed and psychological distress sometimes appears...

Este trabalho objetiva refletir sobre a efetivação das ações de cuidado em saúde mental no Centro de Atenção Psicossocial Infantojuvenil (CAPSi) e sua intersecção com a lógica da Atenção Psicossocial. Construída no bojo do Movimento da Reforma Psiquiátrica brasileira, a Atenção Psicossocial vem sendo definida como um conjunto de ações capazes de constituírem um novo paradigma para as práticas em saúde mental que supera o modelo manicomial. Entre as ações alvitradas nesse processo, o CAPSi, parte da rede de serviços substitutiva, vem sendo considerado a iniciativa mais concreta do Estado de deslocar para a esfera pública o cuidado com a saúde mental de crianças e adolescentes em sofrimento psíquico grave e persistente, impossibilitados ou afetados de alguma forma em sua condição de manter ou estabelecer laços sociais e projetos de vida. A Atenção Psicossocial pleiteia que o CAPSi não se resuma a um mero serviço, e rompendo com o trabalho médico-centrado, especializado e individualizado, medeie a (re)inserção social e comunitária, agenciando a organização de uma rede ampliada de cuidados. Orientados pela perspectiva sócio-histórica buscamos as cocnepções que demarcam as práticas vigentes e para tanto, acessamos fontes documentais do CAPSi com vistas a identificar o perfil das crianças e adolescentes encaminhados, quais instituições os encaminham, quais motivos os levam a configurarem demanda para atendimento e quais desfechos tiveram seus casos. Ademais, realizamos Grupos de Discussão (GD) com os profissionais do CAPSi e acompanhamos, por meio da observação participante, a rotina de trabalho da equipe e sua inserção em encontros multiprofissionais realizados na Rede de Atenção Psicossocial (RAPS). A inserção no campo nos apresentou concepções de infância, adolescência e saúde mental que naturalizados delineiam a seu modo o teor das práticas...
Keywords: Saude mental infantil; Saúde pública; Reforma psiquiátrica; Serviços de saude mental; Public health